In situ, non-invasive novel measurement method for the determination of integrated waveguide losses - Hack, Michael; Kugler, Bennet; Wanitzek, Maurice; Vijayan, Ponraj; Schulze, Jörg; Oehme, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
We demonstrate an in situ, non-invasive measurement method to ensure stable manufacturing and quality control of integrated waveguides. This method assumes that the scattered light from a waveguide is proportional to the propagating light inside the waveguide. Consequently, we can estimate the waveguide losses by measuring the scattered light along the waveguide. We compare this newly demonstrated measurement method with state-of-the-art methods, including Fabry-Perot interferometry, Mach-Zehnder Interferometry, ring resonator interferometry, and the cut-back method. To validate our measurement method's working principle, we fabricated multiple amorphous silicon waveguides and characterized them using both, the presented and the cut-back method. Both methods yielded comparable results, indicating losses of around 1 dB/cm. For further investigation, multiple measurements of the same sample were conducted, resulting in a standard deviation of 0.29 dB/cm to 0.60 dB/cm. These initial standard deviations are sufficient to verify the presented measurement method. However, we want to emphasize that the main source of these deviations is due to the used measurement setup, indicating that the method has potential for improvement. Nevertheless, we have demonstrated that an in situ, non-invasive measurement of integrated waveguide losses is possible.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Amorphous silicon; Integrated optics; Photonic integrated circuit; Silicon Photonics; Waveguides